Balancing spatially regulated β‐actin translation and dynamin‐mediated endocytosis is required to assemble functional epithelial monolayers. Issue 12 (22nd December 2015) - Cruz, Lissette A.; Vedula, Pavan; Gutierrez, Natasha; Shah, Neel; Rodriguez, Steven; Ayee, Brian; Davis, Justin; Rodriguez, Alexis J.
Abstract : Regulating adherens junction complex assembly/disassembly is critical to maintaining epithelial homeostasis in healthy epithelial tissues. Consequently, adherens junction structure and function is often perturbed in clinically advanced tumors of epithelial origin. Some of the most studied factors driving adherens junction complex perturbation in epithelial cancers are transcriptional and epigenetic down‐regulation of E‐cadherin expression. However, numerous reports demonstrate that post‐translational regulatory mechanisms such as endocytosis also regulate early phases of epithelial‐mesenchymal transition and metastatic progression. In already assembled healthy epithelia, E‐cadherin endocytosis recycles cadherin‐catenin complexes to regulate the number of mature adherens junctions found at cell–cell contact sites. However, following de novo epithelial cell–cell contact, endocytosis negatively regulates adherens junction assembly by removing E‐cadherin from the cell surface. By contrast, following de novo epithelial cell–cell contact, spatially localized β‐actin translation drives cytoskeletal remodeling and consequently E‐cadherin clustering at cell–cell contact sites and therefore positively regulates adherens junction assembly. In this report we demonstrate that dynamin‐mediated endocytosis and β‐actin translation‐dependent cadherin–catenin complex anchoring oppose each other following epithelial cell–cell contact. Consequently, the final extent of adherens junction assembly depends on which of these processes is dominant following epithelial cell–cell contact. We expressed β‐actin transcripts impaired in their ability to properly localize monomer synthesis (Δ3′UTR) in MDCK cells to perturb actin filament remodeling and anchoring, and demonstrate the resulting defect in adherens junction structure and function is rescued by inhibiting dynamin mediated endocytosis. Therefore, we demonstrate balancing spatially regulated β‐actin translation and dynamin‐mediated endocytosis regulates epithelial monolayer structure and barrier function. © 2015 Wiley Periodicals, Inc.